Social influence in the global diffusion of alternative fuel vehicles - a meta-analysis - Pettifor, HJ; Wilson, C; Axsen, J; Abrahamse, W; Anable, J (Elsevier, 2017)
Alternative fuel vehicle technologies are needed to mitigate rising greenhouse gas emissions from transport. Social influence is integral to the diffusion of private vehicles which are highly visible and fulfil practical as well as social functions. This paper provides the first meta-analysis of empirical studies which measure the strength of social influence on consumer vehicle choice. A systematic literature review identified 21 studies that examined three types of social influence: interpersonal communication; neighbourhood effect; and conformity with social norms. A random effects meta-analysis found a significant and small to moderate effect of social influence on vehicle choices (r = 0.241, p < 0.001). The overall effect size did not vary significantly between types of social influence nor between types of vehicle (conventional or alternative fuel). However, further analysis using meta-regression found that heterogeneity in social influence effect size across studies was explained by differences in countries’ cultural receptiveness to normative influence. These findings have important implications for policy and modelling analysis of alternative fuel vehicle adoption, for which diffusion is both a socially and culturally-mediated process.